Acute effects of the use of external instability generating devices on neuromuscular performance - Guillermo Peña García-Orea; Marta Silva Santos; Juan Ramón Heredia Elvar; Marzo Edir Da Silva-Grigoletto (Universidade Federal de Santa Catarina, 2016)
Physical training with the use of instability generator devices has become popular in the health area, in sport training and clinical practice (mainly in the prevention and treatment of injuries). To understand how the process of using these devices occurs and the results of their acute effects is important to guide professionals in choosing the appropriate device. The aim of this review was to present the main features of instability devices and analyze their acute effects on core muscle activation, neuromuscular performance and activation of lower and upper limbs. Studies have shown that the main acute effects of exercises performed with these devices are: 1) increased activation / muscular recruitment (especially in the middle zone or core); 2) greater co-activation of antagonist muscles (trunk, upper and lower limbs), with increased stiffness and joint stability; 3) lower force output, power and speed in extremities.